Application of silica (SiO2) nanofluid and Gemini surfactants to improve the viscous behavior and surface tension of water-based drilling fluids - Abang, G. N. -O.; Pin, Y. S.; Ridzuan, N. (Egyptian Petroleum Research Institute, 2021)
Further studies into drilling fluids especially to reduce the use of oil and synthetic-based drilling fluids are ever-growing due to their contributions to environmental pollution. This study, therefore, attempts to evaluate the thermal, viscosity, surface tension, and filtration loss properties of water-based drilling fluids (WBDFs) upon the addition of Gemini surfactant-silica nanofluid. This surfactant-nanofluid was formed by dissolving silica nanofluid in the surfactant solution, and ultra-sonication was used to attain homogeneity. Characterization of the Gemini surfactant-silica (SiO2) nanofluid was done by Fourier Transform Infrared Spectroscopy (FTIR). The viscosity, surface tension, and filtration loss properties were studied using the rheometer, tensiometer, and low-pressure, low-temperature (LPLT) filter press respectively. The experimental results showed that Gemini surfactants contributed to the highest increase in drilling fluid viscosity compared to a conventional surfactant. Also, when combined with silica-nanoparticles showed better thermal stability with an 11% average change in viscosity with increasing temperature and a decrease in surface tension and filtration loss both showing a 17% and 12% decrease respectively.